Kefiran biopolymer: Evaluation of its physicochemical and biological properties - Radhouani, H. (2018)
Kefiran, an exopolysaccharide produced by lactic acid bacteria, has received a great interest due to a variety of health claims. In this study, we aim to investigate the physicochemical and biological properties of Kefiran polysaccharide extracted from Portuguese kefir grains. The kefir growth rate was about 56% (w/w) at room temperature and the kefir pH after 24 h was about 4.6. The obtained yield of Kefiran polysaccharide extracted from the kefir grains was about 4.26% (w/w). The Kefiran structural features were showed in the 1H nuclear magnetic resonance spectrum. The bands observed in the infrared spectrum confirmed that the Kefiran had a β-configuration; and the X-ray photoelectron spectroscopy analysis confirmed the structure and composition of Kefiran and revealed a C/O atomic ratio of 1.46. Moreover, Kefiran showed an average molecular weight (Mw) of 534 kDa and a number-average molecular weight (Mn) of 357 kDa. Regarding the rheological data obtained, Kefiran showed an interesting adhesive performance accompanied by a pseudoplastic behavior, and the extrusion force of Kefiran was 1 N. Furthermore, Kefiran exhibited a higher resistance to hyaluronidase degradation than hyaluronic acid. Finally, Kefiran showed a lack of cytotoxic response through its ability to support metabolic activity and proliferation of L929 cells, and had no effect on these cells’ morphology. Our research suggested that Kefiran polymer has attractive and interesting properties for a wide range of biomedical applications, such as tissue engineering and regenerative medicine.